How to weep in public : feeble offerings on depression from one who knows - Novak, Jacqueline (2016)
"In her hilarious memoir-meets-guide-to-life, comedian (and depressed person) Jacqueline Novak reveals depression's hidden pleasures, advises readers on how to make most of a cat hair-covered life, and helps them summon the strength to shed that bathrobe and face the world. Exhausted? Rundown? Filled with a vague sense of ennui, an occasional twinge of regret, or a hell of a lot of mood stabilizers? Then this is the book for you. How to Weep in Public is both a tongue-in-cheek advice guide (from a person who has no business giving advice to anyone!) and one woman's breathless journey to consistently put on pants, or at least get out of bed in the morning. Beginning with her earliest blue moments of infancy, and hop-scotching through her exploration of the world of pharmaceuticals, before bounding right back to her parents' couch, Jacqueline Novak will introduce you to the ABC's (Adderall! Benzos! Catatonia!) of depression and reveal, funnily enough, that a lot can happen even when you're standing still. Or, as it happens, lying down. Whether you're coping with the occasional down day, or thrive fully in Picasso's blue period, How to Weep in Public is the perfect place to regroup between those nagging Tony Robbins tapes and that exhausting amount of Leaning In. So sit back, relax, and let Jacqueline Novak teach you how to carpe depressem with the rest of them"--
Keywords: Novak, Jacqueline; Comedians -- United States -- Biography; Depression, Mental -- Humor; HUMOR / Form / Parodies; HUMOR / Topic / Adult; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs